Sex difference and intra-operative tidal volume: Insights from the LAS VEGAS study. Issue 10 (October 2021) - Nijbroek, Sunny G.; Hol, Liselotte; Swart, Pien; Hemmes, Sabrine N.T.; Serpa Neto, Ary; Binnekade, Jan M.; Hedenstierna, Goran; Jaber, Samir; Hiesmayr, Michael; Hollmann, Markus W.; Mills, Gary H.; Vidal Melo, Marcos F.; et al.
Abstract : BACKGROUND: One key element of lung-protective ventilation is the use of a low tidal volume ( V T ). A sex difference in use of low tidal volume ventilation (LTVV) has been described in critically ill ICU patients. OBJECTIVES: The aim of this study was to determine whether a sex difference in use of LTVV also exists in operating room patients, and if present what factors drive this difference. DESIGN, PATIENTS AND SETTING: This is a posthoc analysis of LAS VEGAS, a 1-week worldwide observational study in adults requiring intra-operative ventilation during general anaesthesia for surgery in 146 hospitals in 29 countries. MAIN OUTCOME MEASURES: Women and men were compared with respect to use of LTVV, defined as V T of 8 ml kg −1 or less predicted bodyweight (PBW). A V T was deemed 'default' if the set V T was a round number. A mediation analysis assessed which factors may explain the sex difference in use of LTVV during intra-operative ventilation. RESULTS: This analysis includes 9864 patients, of whom 5425 (55%) were women. A default V T was often set, both in women and men; mode V T was 500 ml. Median [IQR] V T was higher in women than in men (8.6 [7.7 to 9.6] vs. 7.6 [6.8 to 8.4] ml kg −1 PBW, P  < 0.001). Compared with men, women were twice as likely not to receive LTVV [68.8 vs. 36.0%; relative risk ratio 2.1 (95% CI 1.9 to 2.1), P  < 0.001]. In the mediation analysis, patients' height and actual body weight (ABW) explained 81 and 18% of the sex difference in use of LTVV, respectively; it was not explained by the use of a default V T . CONCLUSION: In this worldwide cohort of patients receiving intra-operative ventilation during general anaesthesia for surgery, women received a higher V T than men during intra-operative ventilation. The risk for a female not to receive LTVV during surgery was double that of males. Height and ABW were the two mediators of the sex difference in use of LTVV. TRIAL REGISTRATION: The study was registered at Clinicaltrials.gov, NCT01601223 Abstract : Supplemental Digital Content is available in the text